2023
DOI: 10.1186/s12916-023-03157-2
|View full text |Cite
|
Sign up to set email alerts
|

Have there been sustained impacts of the COVID-19 pandemic on trends in smoking prevalence, uptake, quitting, use of treatment, and relapse? A monthly population study in England, 2017–2022

Sarah E. Jackson,
Harry Tattan-Birch,
Lion Shahab
et al.

Abstract: Background Studies conducted during the early stages of the pandemic documented mixed changes in smoking behaviour: more smokers quitting successfully but little change in prevalence. This study aimed to examine whether there have been sustained impacts of the COVID-19 pandemic on smoking patterns in England. Methods Data were from 101,960 adults (≥ 18 years) participating in the Smoking Toolkit Study, a monthly representative household survey, bet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Previous analyses of data from the Smoking Toolkit Study suggested that smoking rates may have increased among young adults in England during the early stages of the COVID-19 pandemic [ 21 , 33 ]. However, the uncertain rise in smoking we observed among more advantaged women of reproductive age does not appear to have been driven by the pandemic: changes in smoking prevalence since the start of the pandemic were similar in this group to those among all adults and men of the same age from more advantaged social grades.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analyses of data from the Smoking Toolkit Study suggested that smoking rates may have increased among young adults in England during the early stages of the COVID-19 pandemic [ 21 , 33 ]. However, the uncertain rise in smoking we observed among more advantaged women of reproductive age does not appear to have been driven by the pandemic: changes in smoking prevalence since the start of the pandemic were similar in this group to those among all adults and men of the same age from more advantaged social grades.…”
Section: Discussionmentioning
confidence: 99%
“…However, they largely mirrored changes observed among all adults, which were likely linked to the COVID-19 pandemic. A recent study found the start of the Covid-19 pandemic was associated with sustained increases in quitting among adults in England [ 33 ]. Our data show a similar pattern among women of reproductive age.…”
Section: Discussionmentioning
confidence: 99%
“…To date, smoking prevalence among young people in England has remained low despite an increase in vaping prevalence, 2 although there are warning signs that the decline in smoking may have leveled off or reversed in recent years. 2 , 34 There is a need to clearly communicate the risks of vaping compared with smoking to ensure this pattern does not change.…”
Section: Discussionmentioning
confidence: 99%
“…A decades long decline in smoking has stalled in England since the covid pandemic, a study reported in BMC Medicine 1. Researchers at University College London surveyed nearly 102 000 adults from 2017 to 2022 and found that smoking prevalence fell by 5.2% a year but that this rate of decline slowed to 0.3% during the pandemic (April 2020 to August 2022).…”
Section: Smokingmentioning
confidence: 99%